Outcomes Analysis in Epistaxis Management: Development of a Therapeutic Algorithm. Issue 3 (13th June 2013) - Shargorodsky, Josef; Bleier, Benjamin S.; Holbrook, Eric H.; Cohen, Jeffrey M.; Busaba, Nicolas; Metson, Ralph; Gray, Stacey T.
Abstract : Objective: This study explored the outcomes of epistaxis treatment modalities to optimize management and enable the development of a therapeutic algorithm. Study Design: Case series with chart review. Setting: Tertiary care hospital. Subjects and Methods: Adult patients presenting between 2005 and 2011 with epistaxis underwent cauterization, tamponade, and/or proximal vascular control. Outcomes of treatment modalities were compared. Multivariate logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs), adjusting for coagulopathy, hypertension, and bleeding site. Results: The population included 147 patients (94 men, 53 women). For initial epistaxis, nondissolvable packing demonstrated the highest initial treatment failure rate of 57.4% (OR, 3.37; 95% CI, 1.33‐8.59 compared with cautery). No significant differences were noted among initial posterior epistaxis treatment modalities. Length of nondissolvable pack placement for 3, 4, or 5 days had no significant impact on recurrence. Among patients who failed initial management, those who next underwent cautery or proximal vascular control required a significantly shorter inpatient stay of 5.3 vs 6.8 days compared with those who underwent packing (OR, 0.16; 95% CI, 0.04‐0.68). There were no treatment failures following surgical arterial ligation. Conclusion: Initial management of anterior epistaxis with chemical cautery had a higher success rate and a lower number of total required interventions than did nondissolvable packing. Duration of packing did not affect recurrence. In patients who failed initially, progression to cautery or proximal vascular control led to significantly shorter inpatient stays than did packing.